2021
DOI: 10.1111/bph.15659
|View full text |Cite
|
Sign up to set email alerts
|

Platelet inhibition by P2Y12 antagonists is potentiated by adenosine signalling activators

Abstract: The data that support the findings of this study are available from the corresponding author upon reasonable request. Some data may not be made available because of privacy or ethical restrictions. Ethics approval statementUse of human blood samples was approved by St Thomas's Hospital Research Ethics Committee (Ref. 07/Q0702/24) and all studies were conducted in accordance with the Declaration of Helsinki. Conflict of interest disclosureThe authors state that they have no conflict of interest. Declaration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Compared with the control group, the level of ADP, ATP, TGF-β, and P-selectin in the platelets group was significantly elevated, which resulted from platelet activation via ADP contained in the culture medium of 4T1 cells. However, the level of ADP, ATP, TGF-β, and P-selectin in the platelets + Tig statistically equaled to the level of the control group, illustrating that Tig could inhibit the activation of platelets, which was consistent with previous research …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Compared with the control group, the level of ADP, ATP, TGF-β, and P-selectin in the platelets group was significantly elevated, which resulted from platelet activation via ADP contained in the culture medium of 4T1 cells. However, the level of ADP, ATP, TGF-β, and P-selectin in the platelets + Tig statistically equaled to the level of the control group, illustrating that Tig could inhibit the activation of platelets, which was consistent with previous research …”
Section: Resultssupporting
confidence: 91%
“…However, the level of ADP, ATP, TGF-β, and P-selectin in the platelets + Tig statistically equaled to the level of the control group, illustrating that Tig could inhibit the activation of platelets, which was consistent with previous research. 60 We further investigated the effects of pDTA-Tig@CML on the interactions between platelets and tumor cells through the bioactivating release of Tig in vitro. As shown in Figure 2I, platelets adhered to tumor cells in the saline group.…”
Section: Tig Antiplatelet Effects In Tumor Cell Adhesionmentioning
confidence: 99%
“…The reasons for this trend are not completely understood, but it could be that, at higher concentrations, the platelet P2Y1 receptor undergoes desensitisation and internalisation following ligand stimulation (Baurand et al ., 2005; Hardy et al ., 2005). Alternatively, high ligand concentrations might act as a self-regulatory mechanism to supress further platelet activation, since interaction between P2YR and adenosine (released or metabolised) signalling pathways (that inhibit both haemostasis and inflammatory events) has been reported (Shih et al, 2021; Layland et al, 2014). Like ADP, NAD + , ADP-ribose and Up4A induced chemotaxis via Rac1 and RhoA-dependent signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets express two types of adenosine receptors, viz., A 2A (A 2A AR) and A 2B (A 2 BAR) 42 . The binding of adenosine to its receptors causes inhibition of platelet activation and aggregation by increasing the intraplatelet levels of cAMP 43 . It is reported that the general adenosine receptors agonist 5′‐N‐ethylcarboxamidoadenosine (NECA) inhibited human platelet activation and reduced platelet aggregation and collagen secretion via inhibiting the eicosanoid lipid thromboxane A 2 (TXA 2 ) and its associated signaling 44 …”
Section: Platelets Functionmentioning
confidence: 99%